Individual Cultural Values and Profit Expectations on Investment Intentions in Crypto Currency: Religiosity as a Moderating Variable - Abadi, M. Kurnia Rahman; Hamdan, Hamdino Bin (Universitas Muhammadiyah Jakarta, 2023)
This study intends to investigate the effects of conscious and unconscious processes on crypocurrency investment intention. The impact of personal cultural values, profit expectations, and religiosity on intentions for hazardous investments was examined within this paradigm. Additionally, the mediating function of profit expectations in the association between a person's cultural values and religion for crypocurrency investment intents was also examined. Additionally, the topic of religion as a mediator of profit expectations and crypocurrency investing purpose was covered. When our graduate students willingly shared the online survey link on their social networks between February and July 2022, the data were gathered. In all, 446 people responded to the questionnaire in this manner. The AMOS programme was used to carry out structural equation modelling (SEM), which was used to test the research model.In addition to these, the effects of age, education level, sex, and marital status on individual cultural values and investment intentions were examined. The age group of 41 to 50 years old had the highest uncertainty avoidance level. People above the age of 41 had the highest level of long-term orientation. The 51-year-old age group had the least risky investing objectives. Age did not influence collectivism or power distance. The amount of schooling had no impact on any variations in the pertinent variables. Intention to take risks, power distance, masculinity, and collectivism are all greater in men than in women, and married people are more likely to avoid uncertainty and to identify as men than unmarried people. This study is the first to examine the combined effect of conscious and unconscious processes on cryptocurrency investing intentions. The authors have also offered evidence for the presence of a link between these three factors. On the other hand, the number of empirical studies examining the relationship between profit expectancy, religion, and investment intention in cryptocurrency is rather small.